Greenland Ice Core Record of Last Glacial Dust Sources and Atmospheric Circulation. Issue 15 (5th August 2022) - Újvári, G.; Klötzli, U.; Stevens, T.; Svensson, A.; Ludwig, P.; Vennemann, T.; Gier, S.; Horschinegg, M.; Palcsu, L.; Hippler, D.; Kovács, J.; Di Biagio, C.; et al.
Abstract: Abrupt and large‐scale climate changes have occurred repeatedly and within decades during the last glaciation. These events, where dramatic warming occurs over decades, are well represented in both Greenland ice core mineral dust and temperature records, suggesting a causal link. However, the feedbacks between atmospheric dust and climate change during these Dansgaard–Oeschger events are poorly known and the processes driving changes in atmospheric dust emission and transport remain elusive. Constraining dust provenance is key to resolving these gaps. Here, we present a multi‐technique analysis of Greenland dust provenance using novel and established, source diagnostic isotopic tracers as well as results from a regional climate model including dust cycle simulations. We show that the existing dominant model for the provenance of Greenland dust as sourced from combined East Asian dust and Pacific volcanics is not supported. Rather, our clay mineralogical and Hf–Sr–Nd and D/H isotopic analyses from last glacial Greenland dust and an extensive range of Northern Hemisphere potential dust sources reveal three most likely scenarios (in order of probability): direct dust sourcing from the Taklimakan Desert in western China, direct sourcing from European glacial sources, or a mix of dust originating from Europe and North Africa. Furthermore, our regional climate modeling demonstrates the plausibility of European or mixed European/North African sources for the first time. We suggest that the origin of dust to Greenland is potentially more complex than previously recognized, demonstrating more uncertainty in our understanding dust climate feedbacks during abrupt events than previously understood. Plain Language Summary: Abrupt climate change represents an existential threat to civilization. However, the feedbacks that modulate these abrupt changes are poorly understood, undermining our ability to predict future events. Last glacial Greenland ice core records show abrupt climate events coupled to changes in abundance of atmospheric mineral dust, but how dust impacts these events is unclear as the processes involved in dust emission remain elusive. Here we apply multiple novel tracers of dust provenance as well as regional dust cycle modeling to address this uncertainty. We show that the dominant model of mixed East Asian and Pacific volcanic sources to Greenland dust is not supported. Instead, multiple other source scenarios are plausible, demonstrating far more uncertainty in dust climate feedbacks than previously understood. Key Points: Hf–Nd isotope data demonstrate that Central Greenland last glacial dust is not sourced from mixed SE Asian and circum‐Pacific volcanic dust Most likely sources are the Taklimakan in SE Asia, European and/or North African glacial dust deposits based on Hf–Sr–Nd and D/H isotopes Model simulations show that sourcing of North Greenland Ice Core Project ice core dust from Europe is plausible, the addition of North African dust cannot be excluded